SEED HEALTHY TEST AND LEAKAGE RATE OF MEMBRANE USING CONDUCTIVITY TEST ON PEANUT LOCAL VARIETY â€œWALAKARIâ€ EAST SUMBA: PENGUJIAN KESEHATAN BENIH DAN TINGKAT KEBOCORAN MEMBRAN MELALUI CONDUCTIVITY TEST PADA KACANG TANAH VARIETAS LOKALâ€WALAKARIâ€ SUMBA TIMUR - Lusia Danga Lewu (Jurnal Agro Indragiri, 2022)
ABSTRACT Quality seeds are the main factor in supporting the success of production in agriculture. East Sumba has one of the local varieties of peanuts called â€œWalakariâ€. However, the problem is that there is a decrease in yield among farmers caused by the quality of the seeds used having decreased. Seeds that are stored for too long will experience seed deterioration. The aim of the study was to determine the quality of the local variety Walakari peanut as a typical bean of East Sumba through seed health and electrical conductivity tests to see the level of leakage of the seed membrane. The study used a completely randomized design with 10 treatments, 2 replications consisting of P0 (control), P1 (coconut water immersion 50ml/L aquadest), P2 (coconut water immersion 150ml/L aquadest), P3 (coconut water immersion 250ml/L aquadest) , P4 (betel leaf extract immersion 50ml/L aquadest), P5 (betel leaf extract immersion 150ml/L aquadest), P6 (betel leaf extract immersion 250ml/L aquadest), P7 (50ml/L aquadest chili extract), P8 ( 150ml/L aquadest chili extract, P9 (250ml/L aquadest chili extract). The results of the seed health test showed that the Walakari variety was included in the moderate to severe infection category. However, with the immersion treatment of local ingredients, betel leaf extract was able to suppress the spread of disease-causing microorganisms up to 96%. Meanwhile, the results of the membrane leakage test using the conductivity test showed that the average value of the electrical conductivity of Walakari variety peanut seeds in all treatments was included in the high category, except for the betel leaf extract soaking treatment. High conductivity values â€‹â€‹indicate low seed vigor.